METASOMATIC NATURE OF THE ULTRAPOTASSIC GRANITES OF WESTERN TRANSBAIKALIA - Kopylov E.N. (My University, 1989)
Rocks with anomalously high potassium contents, corresponding in normative composition to granites and called ultrapotassic liparite, bolgarite or selengite are known in several areas of the Soviet Union and abroad. It is generally thought that these rocks are of igneous origin, even though it is difficult to explain the mechanism by which their parent ultrapotassic melts may have been generated. However, a convergence of genetic properties which are indicative of the origin of ultrapotassic granites militates against this view.